PENERAPAN SISTEM BASIS DATA DALAM PENGELOLAAN ANGGARAN PEMELIHARAAN JALAN DI KOTA SEMARANG: PENERAPAN SISTEM BASIS DATA DALAM PENGELOLAAN ANGGARAN PEMELIHARAAN JALAN DI KOTA SEMARANG - Rendy Dwi Pangesti; Dianita Ratna Kusumastuti; Baiq Heny Sulistiawati; Rifqi Aulia Abdillah; Delila Jelita Ayu; Belifa Rahma Putri (Bangun Rekaprima, 2025)
Improperly managed road conditions have led to increased maintenance costs and a decline in transportation service quality in Semarang City. Inefficiencies in road maintenance budget managementee often occur due to limited data availability and the lack of an integrated system. This study aims to implement a database system for managing road maintenance budgets using the Provincial Kabupaten Road Management System (PKRMS) developed with Microsoft Access. The research methodology involves the collection of primary data through field surveys and road condition inventories, as well as secondary data obtained from relevant government agencies. The collected data were processed within the PKRMS framework to generate cost estimates for maintenance activities categorized as routine maintenance, periodic maintenance, rehabilitation, and road widening. The analysis results show that road segments with severe damage require the highest budget allocation, particularly for rehabilitation work, whereas roads in good condition only require routine maintenance with relatively lower costs. The implementation of this database system has proven effective in improving efficiency, accuracy, and transparency in the planning and decision-making process for road maintenance budget allocation in Semarang City.